1999
DOI: 10.1088/0022-3727/32/6/013
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the plasma-particle interactions in a plasma jet

Abstract: This study is a first step in modelling plasma particles. We present in this study a two-dimensional modelling of the influence of injection of iron and alumina particles on a d.c. plasma jet in a given geometry which does not correspond to a currently used technology. We would like to point out that we do not try here to duplicate a given technological torch. The inlet gas is argon at atmospheric pressure. The presence of the particles, injected in the jet at the exit of the torch, is taken into account by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…The 3D heat transfer and flow patterns, as well as the ionization-recombination process, inside a thermal plasma torch also have significant effects on the characteristics of the thermal plasma jet issuing from the exit of the plasma torch and, for example, on the quality of the coatings obtained by plasma spray. Over the past few decades, many papers have been devoted to modeling of the DC arc plasma spray process or to the study of spray-related basic processes based on 2D (axi-symmetrical) assumption with neglecting the effects of the transverse injection of the cold carrier gas on the jet flow field and on particle behavior ( Ref 4,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. But experimental results showed that even a small amount of carrier gas (5% of the main flow) transverse injection, as well as the particles used as the tracers in LDV measurements, may induce a deflection of the plasma jet with a deflection angle as great as 5°, and this 3D effect must be taken into account in the interpretation of the LDV data ( Ref 35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D heat transfer and flow patterns, as well as the ionization-recombination process, inside a thermal plasma torch also have significant effects on the characteristics of the thermal plasma jet issuing from the exit of the plasma torch and, for example, on the quality of the coatings obtained by plasma spray. Over the past few decades, many papers have been devoted to modeling of the DC arc plasma spray process or to the study of spray-related basic processes based on 2D (axi-symmetrical) assumption with neglecting the effects of the transverse injection of the cold carrier gas on the jet flow field and on particle behavior ( Ref 4,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. But experimental results showed that even a small amount of carrier gas (5% of the main flow) transverse injection, as well as the particles used as the tracers in LDV measurements, may induce a deflection of the plasma jet with a deflection angle as great as 5°, and this 3D effect must be taken into account in the interpretation of the LDV data ( Ref 35).…”
Section: Introductionmentioning
confidence: 99%
“…In Recent years, 3D modeling work concerning the effects of transverse gas injection from a single injection port on the plasma jet characteristics and the trajectories of injected particles attracted increasing interest (Ref [44][45][46][47][48][49][50][51][52]. The common feature of most of these papers is that assumed 2D temperature and velocity distributions at the outlet of the torch nozzle (or the inlet of the plasma jet region) are employed as boundary conditions for 3D modeling of heat transfer, flow patterns, and particle behavior in the jet region, i.e., only the effect of the carrier gas injection on the 3D characteristics of the plasma jet is included in the modeling work (Ref [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Using velocity and temperature profiles obtained from modeling of DC arc plasma torches as the starting conditions of plasma jets (Ref 4,53) depends strongly on the ability to model plasma torches.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the system is composed of three common conservation equations: mass, momentum and energy coupled to the ad hoc Maxwell's equations [1][2][3][4] (depending on the problem). To these equations, a set of complementary equations is added to take into account other electrical or thermal phenomena depending on the application: 5-7 turbulence effects, 8 deviations from chemical equilibrium or thermal equilibrium, 9 modelling of multiphase flows, role of the shielding gases, 10 interactions arcanode/cathode, 11-13 interaction plasma-walls and/or plasma-particles, [14][15][16] diffusion of the gaseous species or particles in the plasma, 17 formation of fume or nucleation/growth/aggregation of particles 18,19 are some examples. The equations of the system can be written as a convection-diffusion equation (1) for a variable φ.…”
Section: Use Of Radiative and Transport Coefficients In Thermal Pmentioning
confidence: 99%
“…Thermal plasmas can also be generated by several methods such as dc electrical discharges at current intensities higher than a few amperes and up to 10 5 A, free burning arcs [1], [2], transferred arcs [3], [4], or nontransferred plasma torches [5]- [8], [10], [11], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 25 years or so, many papers describing the 2-D numerical modeling of plasma torches have been published [1]- [3], [5], [6], [8], [11], where the assumption of azimuthally symmetric variables is made. The 2-D approach thus ignores many phenomena, which are essentially asymmetric with respect to θ-variations.…”
Section: Introductionmentioning
confidence: 99%